2017
DOI: 10.15179/ces.19.2.2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Membership in Strategic Alliances on the Profitability of Firms in the Retail Sector

Abstract: Strategic alliances in the retail sector are based on cooperation in a variety of activities, ranging from supply and marketing to knowledge sharing and branding. For their members, they are a source of sustainable competitive advantage. Ever since the 1990s, a growing number of firms from the retail sector have attempted to improve their performance through participation in strategic alliances. The objective of this paper is to explore how participation in strategic alliances influences profitability of firms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…This finding is significant and positive, and this indicates that strategic alliance affects the growth of profit in SMEs. This also corroborates the work of Butigan and Benic (2017) who found that there is a positive relationship between participation in strategic alliances and firm profitability. This can be attributed to reduction in production cost, risk sharing, and knowledge transfer, which are positive externalities of strategic alliances.…”
Section: Effect Of Strategic Alliance On the Performance Of Small-and...supporting
confidence: 90%
“…This finding is significant and positive, and this indicates that strategic alliance affects the growth of profit in SMEs. This also corroborates the work of Butigan and Benic (2017) who found that there is a positive relationship between participation in strategic alliances and firm profitability. This can be attributed to reduction in production cost, risk sharing, and knowledge transfer, which are positive externalities of strategic alliances.…”
Section: Effect Of Strategic Alliance On the Performance Of Small-and...supporting
confidence: 90%
“…The strategic alliance is a hybrid between the market and the firm, and can be a means to reduce the sum of transaction and production costs, thus formed to minimize costs and the motive for the theory is the evasion of small number bargaining and opportunism (Kogut, 1988). Therefore, the TCT suggests that the impact of strategic alliances on their members will be positive only if the potential benefits outweigh the costs of participation (Butigan & Benid, 2017), and transaction costs enhance competitive position and the acquisition of knowledge (Arrigo, 2012). Christoffersen (2013) and Shi, Sun, and Prescott (2011) anchored their studies on this theory.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…There are studies on its effect on market share (Enyinnah, et al, 2020), operation sustainability (Akpotu & Jasmine, 2016), aviation industry (Thendu, 2020), small businesses and startups (Cacciolatti, Rosli, Ruiz-Alba, & Chang, 2020;Nwokocha & Madu, 2020;Obioma, 2017;Salisu & Abu Bakar, 2018;Talebi, et al, 2017), as well as on large corporations (Junaidu, et al, 2019). Strategic alliances studies have also been carried out in the service industry (Akewushola, et al, 2018;Akpotu & Jasmine, 2016;Enyinnah, et al, 2020;Salisu & Abu Bakar, 2018), retail (Butigan & Benid, 2017;Muange & Maru, 2015;Yacob, Sucherly, Sari, & Mulyana, 2016), and the manufacturing industry (Akewushola, et al, 2018;Aun, 2014;Ejekwu, Zeb-Obipi, & Uhuru, 2020;Junaidu, et al, 2019;Mathuki et al, 2019;Muteshi & Awino, 2018;Uko & Hamilton, 2020).…”
Section: Empirical Reviewsmentioning
confidence: 99%
See 2 more Smart Citations